The Natural Large Genomic Deletion Is Unrelated to the Increased Virulence of the Novel Genotype Fowl Adenovirus 4 Recently Emerged in China - Pan, Qing (Viruses, 2018)
Since 2015, severe hydropericardium-hepatitis syndrome (HHS), caused by a highly pathogenic fowl adenovirus 4 (FAdV-4), emerged in China. In our previous study, the FAdV-4 has been identified as a novel genotype with a unique 1966-bp nucleotide deletion (1966Del) between open reading frame 42 and 43. In this study, the natural 1966Del was frequently identified among 17 clinical isolates and other reported Chinese clinical strains. To investigate the relationship between 1966Del and the increased virulence of the novel FAdV-4, a CRISPR/Cas9 operating platform for FAdV-4 was developed for the first time in this study. Based on this platform, a Re1966 strain was rescued, inserted the relative 1966Del sequence of a nonpathogenic strain KR5. In the pathogenicity study, the Re1966 strain retained high virulence for specific-pathogen-free chickens, similar to the parental wild-type HLJFAd15, although the survival time of chickens infected with Re1966 was much longer. Therefore, the natural 1966Del was identified as a non-essential site for the increased virulence of the emerged novel FAdV-4. Although further research on the virulence-determining region or point within the genome of the novel FAdV-4 is needed, the CRISPR/Cas9 operating platform for the novel FAdV-4 was developed and successfully applied to edit the genomic DNA for the first time, and it provides a novel powerful tool for both basic virology studies and vaccine vector development of FAdVs.